2015
DOI: 10.1111/1755-0998.12444
|View full text |Cite
|
Sign up to set email alerts
|

Untangling taxonomy: a DNA barcode reference library for Canadian spiders

Abstract: Approximately 1460 species of spiders have been reported from Canada, 3% of the global fauna. This study provides a DNA barcode reference library for 1018 of these species based upon the analysis of more than 30 000 specimens. The sequence results show a clear barcode gap in most cases with a mean intraspecific divergence of 0.78% vs. a minimum nearest-neighbour (NN) distance averaging 7.85%. The sequences were assigned to 1359 Barcode index numbers (BINs) with 1344 of these BINs composed of specimens belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 46 publications
7
97
0
Order By: Relevance
“…Each of the 4.5 million animal records on BOLD has been assigned to a BIN, a Barcode Index Number (Ratnasingham and Hebert 2013), generating 452 000 BINs, predominantly insects (315 000) (accessed 21 April 2016). Because BINs show strong congruence with species designated through past morphological study (Pentinsaari et al 2014;Zahiri et al 2014;Mutanen et al 2015), they can be viewed as species proxies (Telfer et al 2015) to facilitate the assessment of large-scale biodiversity patterns (Blagoev et al 2016) and the detection of cryptic species complexes (Kekkonen and Hebert 2014;Ashfaq et al 2015). The use of barcode data to identify species (Rakauskas and Basilova 2013) as opposed to BINs requires the species in question be represented in the barcode reference library (Ekrem et al 2007).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the 4.5 million animal records on BOLD has been assigned to a BIN, a Barcode Index Number (Ratnasingham and Hebert 2013), generating 452 000 BINs, predominantly insects (315 000) (accessed 21 April 2016). Because BINs show strong congruence with species designated through past morphological study (Pentinsaari et al 2014;Zahiri et al 2014;Mutanen et al 2015), they can be viewed as species proxies (Telfer et al 2015) to facilitate the assessment of large-scale biodiversity patterns (Blagoev et al 2016) and the detection of cryptic species complexes (Kekkonen and Hebert 2014;Ashfaq et al 2015). The use of barcode data to identify species (Rakauskas and Basilova 2013) as opposed to BINs requires the species in question be represented in the barcode reference library (Ekrem et al 2007).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Lineages showing sequence divergence, often termed molecular operational taxonomic units (MOTUs) (Blaxter et al 2005), have been discriminated by analyzing sequence variation using distance analysis (Schloss and Handelsman 2005), neighborjoining clustering (Saitou and Nei 1987), phylogenetic trees (Zhang et al 2013), Bayesian inference (Yang and Rannala 1997), coalescence-based approach (Pons et al 2006;Fujisawa and Barraclough 2013), barcode-gap analysis (Puillandre et al 2012), and BINs (Ratnasingham and Hebert 2013). However, there is a growing trend to integrate multiple methods (Ashfaq et al 2015;Kekkonen et al 2015;Blagoev et al 2016) and multiple markers (Jörger et al 2012;Mrinalini et al 2015) to assess MOTU diversity. The results from such analyses have frequently been helpful in resolving taxonomic problems and in estimating species richness and abundance (Unterseher et al 2011;Mutanen et al 2013;Stahlhut et al 2013).…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…They concluded that there may be more than 100 000 species of insects in Canada, including as many as 50 000 species of Diptera and 30 000 species of Hymenoptera. Similarly, Blagoev et al (2016) used DNA barcoding to conclude that the number of species of spiders in Canada (~1460) may be underestimated by 30-50%.…”
Section: The Prairies Ecozone and Its Constituent Ecoregionsmentioning
confidence: 99%
“…DNA barcoding has been used successfully for specimen identification in many animal groups (Hebert et al 2003, Blagoev et al 2016, including ticks (Erster et al 2013, Lv et al 2014, Lah et al 2016.…”
Section: Dna Barcoding Ticksmentioning
confidence: 99%